Rural tourism: Marketing mix, challenges and benefits in India - Hena M (International Journal of Multidisciplinary Research and Development, 2015)
As is generally agreed rural tourism is one of the main drivers of economic growth and employment generations in more than 80 countries. Predominantly, Indian economy is very much an agriculture economy. Due to the insufficiency of agriculture livelihoods and the search for new sources of growth and economic opportunity for the rural people the policy makers focused more on diversification than regeneration of the rural economy. In this context, rural tourism is promoted as a new activity, which is supplementary to agriculture. There are of course some rural areas that have already been transformed into tourism “destinations” in the country. It has the potential of addressing issues such as rural poverty; employment of women besides strengthening the economic status of rural artisans, earnings foreign exchange etc. The rural tourism has great potentialities in attracting tourists of various interests as it is a mix of various tourism concepts. It provides everything in single package and works in non-urban setting with rural essence for the benefit of local community while preserving rural assets, values and heritage. In the last decade there has been a remarkable increase in the arrival of foreign tourists. Therefore, rural tourism has great potential and can earn high revenue in near future. If India does not take advantage of this tourism revolution, other developing countries will capitalize the current boom in the tourism industry. Hence, this study is to overview the marketing mix of rural tourism and to highlight the challenges and benefit in rural India. The lack of infrastructure is visible in all segments of tourism be it related to airports, railways, surface transport, accommodation, trained manpower, shopping with ease travelling in style, medical tourism, tourism education, sustainable development norms etc. The tourism industry can maximize on the infrastructure development part by providing the priority to tourism tax incentives in private sector, specialized norm for single window clearance for Foreign Direct Investment (FDI), creating suitable lands, banks financial assistance mainly long term loans on low rate of interest, free flow of foreign exchange in the country, involving professionals and less interference with bureaucrats or free from red tape. This is the right approach or only way to boost rural infrastructure, ultimately to develop rural tourism.